Institutional adult education regimes : Continuing vocational education and training participation and barriers in Germany, Sweden, and the United Kingdom - Breznau, Nate [Verfasser]; Offerhaus, Judith [Verfasser] (My University, 2026)
"This study investigates continuing vocational education and training (CVET) in three institutional contexts: Germany, Sweden, and the United Kingdom. Drawing on PIAAC Cycle 1’s unique questions and transparency, we analyse institutional regimes and socio-economic gradients in CVET participation. Barriers to and engagement in CVET is embedded in educational, labour market, and welfare state institutions. Results show that Sweden’s universal-collectivist regime fosters the highest participation with minimal disparities, while Germany’s corporatist regime shows lower participation and higher stratification. The UK’s liberal-individualist model exhibits moderate participation but sharp socio-economic inequalities, emphasising financial and employer-related barriers. Resource constraints such as time and money are prominent barriers across institutional contexts. Our exploratory measurement of CVET interest opens pathways for future research that was not thought possible with existing PIAAC data. These findings contribute to long-term institutional analysis and theory, and inform policy interventions to reduce barriers, increase interest, and support disadvantaged groups." (Author's abstract ; BIBB-Doku)
Keywords: S 1.5 Weiterbildung; S 1.5.2 Berufliche Weiterbildung; I 2.1 Deutschland; I 2.2.1 Westeuropa; G 1.3.2 Bildungsverhalten und -verläufe; 370; Weiterbildungssystem; Berufliche Weiterbildung; Bundesrepublik Deutschland; Schweden; Vereinigtes Königreich; Weiterbildungsbereitschaft; Sozioökonomische Faktoren; PIAAC